An instrument to assess organizational readiness to implement knowledge management process - Mohamed Razi, Mohamed Jalaldeen; Abdul Karim, Nor Shahriza (2010)
The Concept of knowledge management (KM) is highly being studied nowadays as it plays a major role in the competitive business world. Though different aspects of KM are being exposed in the literature, very limited information is available on organizational readiness for KM process implementation. Hence, the present authors propose a research model by integrating knowledge creation theory, KM enablers, and individual acceptance models. In addition, an instrument that can be used to measure the organizational readiness for KM process implementation also presented. The reliability of the proposed instrument is proved after testing it among academic staffs of a Malaysian university.